ANALISIS PERBANDINGAN KINERJA PROTOKOL ON-DEMAND ROUTING PADA JARINGAN SENSOR NIRKABEL AD HOC - Putri, Rizky Ananto; Jusak, Jusak; Sukmaaji, Anjik (Journal of Control and Network Systems, 2013)
Some of developing countries recently employ network applications that use sensor nodes, Wireless Sensor Networks (WSN) for remote sensing. Most latest researchers, utilize methods with a network topology that has a fixed position. On the other hand, for remote monitoring network set up wireless networks typically use ad hoc and irregular distributed by its users. A study needed to create a network system with randomly generated positions. In this work we concern about wireless network that employ On Demand Routing Protocols, i.e. Ad Hoc On-Demand Distance Vector (AODV) and Dynamic Source Routing (DSR). The result of the research shows that DSR has a better performance in term of delay and packet loss ratio compared to the AODV. On the other hand, AODV shows a better performance in term of bandwidth utilization.